THE EFFECT OF CUMIN ON INDUCED DIABETES IN RATS - Omar H. Azeez; Mutaa A. Abed (Basrah Journal of Veterinary Research)
The present study was conducted to evaluate the effect of Cumin on diabetes mellitus induced by alloxan in rats. Male Wister rats were used, and randomly divided into five groups (6-8 rats for each group): The first group: was administered distilled water and served as normal control, the second group: induced diabetes by single subcutaneous injection of alloxan 100 mg/kg.body weight and served as diabetic control, the 3,4,5 groups was administered 50,100,200 gm/kg of rat's forage respectively for four weeks, then diabetes are induced in this groups by same route as above. Cumin treatment in all doses lead to significant decrease glucose levels, and triglyceride and significant decrease in cholesterol level in dose 100, 200 gm/kg of forage and no change occur in total protein level. These results indicate that cumin have a role in delaying of diabetes through the effects of cumin in decrease some biochemical parameters